A Mismatched Group of Items That I Would Not Find Particularly Interesting: Challenges and Opportunities with Digital Exhibits and Collections Labels - Harden, Melissa; Martinez-Montavon, Anna Michelle; Narlock, Mikala (Evidence Based Library and Information Practice, 2022)
Objective – The authors sought to identify link language that is user-friendly and sufficiently disambiguates between a digital collection and digital exhibit platform for users from a R1 institution, or a university with high research activity and doctoral programs as classified in the Carnegie Classification of Institutions of Higher Education.Methods – The authors distributed two online surveys using a modified open card sort and reverse-category test via university electronic mailing lists to undergraduate and graduate students to learn what language they would use to identify groups of items and to test their understanding of link labels that point to digitized cultural heritage items.Results – Our study uncovered that the link terms utilized by cultural heritage institutions are not uniformly understood by our users. Terms that are frequently used interchangeably (i.e., Digital Collections, Digital Project, and Digital Exhibit) can be too generic to be meaningful for different user groups.Conclusion – Because the link terms utilized by cultural heritage institutions were not uniformly understood by our users, the most user-friendly way to link to these resources is to use the term we—librarians, curators, and archivists—think is most accurate as the link text based on our professional knowledge and provide a brief description of what each site contains in order to provide necessary context.